The originalities of ethnically determined psychic phenomena of Aukštaičiai and Žemaičiai individuals - Bliumas, Remigijus (Psichologija, 1997)
The purpose of the research work was to compare psychic characteristics of elderly (60-85 years old) Aukštaičiai (people of the Lithuanian highlands) and Žemaičiai (people of the Lithuanian lowlands). The most important point was to distinguish ethnically determined differences in the research object. The nuli hypothesis on the absence of distinguishing psychic characteristics between the sample of 60 elderly Aukštaičiai individuals and the sample of 60 Žemaičiai individuals was verified by means of empirical research. The Rorschach Inkblot Method and the full Lūscher Color Test were used in the research work. Of 30 examined by Rorschach lnkblot Method variables, 13 showed a statistically significant difference. A representation of 13 variables of the method did not support the nuli hypothesis on the homogeneity of Aukštaičiai and Žemaičiai samples. The variables W, D, Dd, M, H, A, Ad, 11, Z, Egol, IsI, R, and t statistically show significant differences in results of the Aukštaičiai and Žemaičiai investigation. Full Lūscher Color Test results differentiated the groups according to the choice of red color in the basic 8-colour table. According to the results, 3 basic groups of ethnically determined psychic phenomena and their peculiarities were identified, i.e., cognitive processes, emotional experiences, and personality traits. lndividuals belonging to the samples also differed in the character of their relations with the material and social environment. Ethnically determined psychic phenomena and their peculiarities could have formed owing to the influence exercised by variables that fall into 6 groups: the physical environment, social structure, subjective culture, personality, personality predispositions, and accidental factors. The results of the research were fixed as a starting point for exhaustive and long-term ethnopsychological investigations and as tasks to be concluded in further ethnopsychological research in Lithuanian programs.